Factors Influencing Adoption of Chemical Pest Control in Cowpea production among Rural Farmers in Makarfi Local Government Area of Kaduna State, Nigeria - R I Omolehin; T O Ogunfiditimi; O B Adeniji (Journal of Agricultural Extension, 2007)
This study examines the factors influencing the adoption of chemical pest control in cowpeas production in MakarfiLocal Government Area of Kaduna State, Nigeria. Data were collected using stratified random sampling method from 61 farmers adopting chemical pest control and 79 non- adopters making up a total of 140 respondents. A Probit analysis was used to ascertain factors influencing farmers' adoption of chemical pest control while the t-test was used to determine whether there is statistical significant difference between the productivity of adopters and non-adopters to enable us draw inference on the foodsecurity andpoverty reduction ability of the chemicalpest control practice. The results reveals that the adoption of chemical pest control in cowpeas production is influenced by farmers' age, marital status, educational qualification, the desires farmers forhigheryields and the contact with extension activities. The results also helpedto establish that chemicalpest controlcouldhelp the farmers inmakingsure that higher yields are obtained from cowpeasproduction thus helping the rural farmers to become food secured since cowpeas are very goodprotein rich food. Moreover, the result the yields from adopters has shown that the practice couldhelp farmers realize marketable surplus that willlead to higherincome generation thereby reducingpoverty among the ruralfarmers.